Color Enrichment Solids of Spectrally Pure Colloidal Quantum Wells for Wide Color Span in Displays. Issue 14 (6th June 2022) - Erdem, Talha; Soran‐Erdem, Zeliha; Isik, Furkan; Shabani, Farzan; Yazici, Ahmet Faruk; Mutlugün, Evren; Gaponik, Nikolai; Demir, Hilmi Volkan
Abstract: Colloidal quantum wells (CQWs) are excellent candidates for lighting and display applications owing to their narrow emission linewidths (<30 nm). However, realizing their efficient and stable light‐emitting solids remains a challenge. To address this problem, stable, efficient solids of CQWs incorporated into crystal matrices are shown. Green‐emitting CdSe/CdS core/crown and red‐emitting CdSe/CdS core/shell CQWs wrapped into these crystal solids are employed as proof‐of‐concept demonstrations of light‐emitting diode (LED) integration targeting a wide color span in display backlighting. The quantum yield of the green‐ and red‐emitting CQW‐containing solids of sucrose reach ≈20% and ≈55%, respectively, while emission linewidths and peak wavelengths remain almost unaltered. Furthermore, sucrose matrix preserves ≈70% and ≈45% of the initial emission intensity of the green‐ and red‐emitting CQWs after >60 h, respectively, which is ≈4× and ≈2× better than the drop‐casted CQW films and reference (KCl) host. Color‐converting LEDs of these green‐ and red‐emitting CQWs in sucrose possess luminous efficiencies 122 and 189 lm W −1 elect, respectively. With the liquid crystal display filters, this becomes 39 and 86 lm W −1 elect, respectively, providing with a color gamut 25% broader than the National Television Standards Committee standard. These results prove that CQW solids enable efficient and stable color converters for display and lighting applications. Abstract : Green‐ and red‐emitting colloidal quantum wells are wrapped into sucrose host for high efficiency and stability. The green and red light‐emitting diodes of these solids exhibit a color gamut 25% broader than the NTSC color span, with respective luminous efficiencies of 122 and 189 lm W −1 elect before the liquid crystal display (LCD) filters and 39 and 86 lm W −1 elect after the LCD filters.